Application of nitrogen fertilizer in maize in Southern Asia: a review - Shrestha, J. (2018)
The rate, time and method of nitrogen (N) fertilizer application are strongly related to growth, development, and yield of the crop. This study principally focuses on the role of the nitrogen in growth, development, and production of the maize, emphasizing time and methods of fertilizer application and their suitable rates. The review shows that crop yield increases up to certain limit and declines if applied in an excess amount of nitrogen. Nitrogen affects various physiological and biochemical processes in plant cells that ultimately affect the growth and development of the plant. Nitrogen response by maize differs due to growth stages, environment and genotype of maize. Hybrid and improved maize varieties are more nitrogen-responsive than local varieties of maize. Proper nitrogen applications as basal doses at planting stage, split doses at critical growth stages namely knee high, and flowering stages are necessary for higher grain yield. This review serves as a useful tool to maize researchers and growers for making the right decision on nitrogen application on maize.